Illuminance levels based on different sky conditions by considering daylight harvesting - Nik Sahidah Nik Ahmad; N. H. Radzi; Mohd Noor Abdullah (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Daylight harvesting systems (DHS) offer the most effective and significant to reduce energy consumption. In the lighting system, there are various problems which include waste of energy consumption, inappropriate lighting and increasing greenhouse effect. Therefore, the waste of energy consumption should be reduced by controlling the dimming levels of artificial lighting according to the standard thus reducing the greenhouse effect. Hence, this paper considered the daylight adaptive for the lighting system to determine the dimming level and illuminance level for the office room. The simulation has been carried out using DIALux simulation lighting software to simulate the average daylight and average illuminance level with different conditions sky, which is clear, average, and overcast sky. Based on the result, the illuminance level has complied with the European Standard EN12464-1. Furthermore, the presence of daylight and weather conditions plays an essential role in the lighting system. The illuminance and dimming levels are different depending on the time and type of sky condition at that time. Therefore, the daylight adaptive in the lighting system can reduce the use of artificial light in the room.